Spectral properties of single gold nanoparticles in close proximity to biological fluorophores excited by 2-photon excitation - Anzalone, Andrea (2015)
Metallic nanoparticles (NPs) are able to modify the excitation and emission rates (plasmonic enhancement) of fluorescent molecules in their close proximity. In this work, we measured the emission spectra of 20 nm Gold Nanoparticles (AuNPs) fixed on a glass surface submerged in a solution of different fluorophores using a spectral camera and 2-photon excitation. While on the glass surface, we observed the presence in the emission at least 3 components: i) second harmonic signal (SHG), ii) a broad emission from AuNPS and iii) fluorescence arising from fluorophores nearby. When on the glass surface, we found that the 3 spectral components have different relative intensities when the incident direction of linear polarization was changed indicating different physical origins for these components. Then we measured by fluctuation correlation spectroscopy (FCS) the scattering and fluorescence signal of the particles alone and in a solution of 100 nM EGFP using the spectral camera or measuring the scattering and fluorescence from the particles. We observed occasional fluorescence bursts when in the suspension we added fluorescent proteins. The spectrum of these burst was devoid of the SHG and of the broad emission in contrast to the signal collected from the gold nanoparticles on the glass surface. Instead we found that the spectrum during the burst corresponded closely to the spectrum of the fluorescent protein. An additional control was obtained by measuring the cross-correlation between the reflection from the particles and the fluorescence arising from EGFP both excited at 488 nm. We found a very weak cross-correlation between the AuNPs and the fluorescence confirming that the burst originate from a few particles with a fluorescence signal.